Social commerce: Analysing the integration of e-commerce and social media platforms for direct selling and customer acquisition - Beyari, Hasan; Bahaaudeen, Amirah (Journal of Posthumanism, 2025)
This research aimed to analyse the integration of e-commerce and social media platforms for direct selling and customer acquisition. Seven hypotheses were formed to achieve the aim. For this purpose, a survey of 412 social commerce customers and interviews with 24 different types of stakeholders were conducted. The findings supported all seven hypotheses explaining 68% of the variance in customer acquisition effectiveness, 59% in purchasing intentions, 54% in customer engagement, and 37% in trust. Seller responsiveness and secure payment options were the strongest predictors of trust. Customer acquisition was most efficient with influencer partnerships, followed by user-generated content campaigns and live shopping events. While cash on delivery was most preferred, the Mada card is gaining popularity. All these findings were supported by the literature. Thematic analysis of interview responses revealed six themes. They include cultural dimensions of trust building, seamless integration as a competitive advantage, personalisation through social engagement, challenges of platform dependency, regulatory and payment infrastructure gaps, and the evolving role of micro-influencers. These themes were supported by the literature.